2014
DOI: 10.1128/genomea.01108-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Sugar Cane Endophyte Pseudomonas aurantiaca PB-St2, a Disease-Suppressive Bacterium with Antifungal Activity toward the Plant Pathogen Colletotrichum falcatum

Abstract: The endophytic bacterium Pseudomonas aurantiaca PB-St2 exhibits antifungal activity and represents a biocontrol agent to suppress red rot disease of sugar cane. Here, we report the completely sequenced 6.6-Mb genome of P. aurantiaca PB-St2. The sequence contains a repertoire of biosynthetic genes for secondary metabolites that putatively contribute to its antagonistic activity and its plant-microbe interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Bacterial culture-containing plates were incubated at 28 o C for 24 h. CAS medium [27] was overlaid on these cultures, and a change in color from blue to orange (hydroxamate-type siderophore) or purple (catechol-type siderophore) was considered as a positive result. Pseudomonas aurantiaca PB-St2 was used as a positive control [17]. Sterilized LB and water were used as the negative control.…”
Section: Detection Of Hcn and Siderophore Production By Using Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial culture-containing plates were incubated at 28 o C for 24 h. CAS medium [27] was overlaid on these cultures, and a change in color from blue to orange (hydroxamate-type siderophore) or purple (catechol-type siderophore) was considered as a positive result. Pseudomonas aurantiaca PB-St2 was used as a positive control [17]. Sterilized LB and water were used as the negative control.…”
Section: Detection Of Hcn and Siderophore Production By Using Bioassaysmentioning
confidence: 99%
“…The objectives of this study included selection of fluorescent pseudomonads based on antifungal activity against local pathogens; characterization of the selected Pseudomonas isolates; search for those secondary metabolites that have been previously reported for fluorescent pseudomonads [15]; screen for HCN, siderophore production, and phosphate and zinc solubilization by using bioassays; and observation of the effect of these strains on wheat plant growth by inoculation. P. chlororaphis subspecies aurantiaca strain PB-St2 was previously isolated from sugarcane by our laboratory and its secondary metabolites were reported [16][17][18]. In this study, it was used as a reference/standard for phenazines, the cyclic lipopeptide white line-inducing principle (WLIP) and lahorenoic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…aurantiaca PB-St2, the whole genome sequence [13] was analyzed using antiSMASH 3.0 software, which readily identified three putative QS systems. To obtain more information about these systems, a BLAST search for already known and characterized systems was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, strain PB-St2 was shown to produce three aromatic acids called lahorenoic acids A-C, 2-hydroxyphenazine-1-carboxylic acid, 2,8-dihydroxyphenazine, the lipopeptide WLIP, hydrogen cyanide, and C6-homoserine lactone (HSL) [11, 12]. Genome sequencing of PB-St2 revealed that the strain possesses in addition the biosynthetic capacity to produce the antifungal metabolite pyrrolnitrin, and siderophores of the achromobactin and pyoverdin-type [13]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation